The stroke 'Act FAST' campaign: Remembered but not understood?. Issue 3 (6th August 2014) - Dombrowski, Stephan U.; White, Martin; Mackintosh, Joan E.; Gellert, Paul; Araujo‐Soares, Vera; Thomson, Richard G.; Rodgers, Helen; Ford, Gary A.; Sniehotta, Falko F.
Abstract : Background: The stroke awareness raising campaign 'Act FAST' (Face, Arms, Speech: Time to call Emergency Medical Services) has been rolled out in multiple waves in England, but impact on stroke recognition and response remains unclear. Purpose: The purpose of this study was to test whether providing knowledge of the FAST acronym through a standard Act FAST campaign leaflet increases accurate recognition and response in stroke‐based scenario measures. Methods: This is a population‐based, cross‐sectional survey of adults in Newcastle upon Tyne, UK, sampled using the electoral register, with individuals randomized to receive a questionnaire and Act FAST leaflet ( n  = 2500) or a questionnaire only ( n  = 2500) in 2012. Campaign message retention, stroke recognition, and response measured through 16 scenario‐based vignettes were assessed. Data were analyzed in 2013. Results: Questionnaire return rate was 32·3% ( n  = 1615). No differences were found between the leaflet and no‐leaflet groups in return rate or demographics. Participants who received a leaflet showed better campaign recall (75·7% vs. 68·2%, P  = 0·003) and recalled more FAST mnemonic elements (66·1% vs. 45·3% elements named correctly, P  < 0·001). However, there were no between‐group differences for stroke recognition and response to stroke‐based scenarios ( P  > 0·05). Conclusions: Despite greater levels of recall of specific 'Act FAST' elements among those receiving the Act FAST leaflet, there was no impact on stroke recognition and response measures.